Changes in the Polish market for agricultural organic products - Kociszewski, Karol; Graczyk, Andrzej; Sobocińska, Magdalena; Krupowicz, Joanna; Mazurek-Łopacińska, Krystyna (Economics and Environment, 2023)
This paper attempts to identify changes in the factors influencing the functioning and evolution of the Polish market for organic agricultural products. It brings together the results of surveys of farmers (carried out in 2011, 2019, and 2021), distributors (carried out in 2019 and 2021), and consumers (carried out in 2009 and 2021). Initially, farmers believed that the greatest opportunities for market development lay in demand factors, including in particular consumer environmental awareness. In 2021, their opinions worsened in this regard, which means they had difficulties reaching consumers. Another opportunity that was less popular than before was the EU subsidies. This is due to administrative and bureaucratic burdens, which, along with high production costs and weak links between farmers and distributors, were considered to be the biggest barriers to market development. For distributors, the survey produced similar conclusions. According to consumers, the greatest opportunities for market development result from increasing environmental awareness, increased diversity of products and better promotion. The barriers they highlighted include high prices, limited environmental education, lack of adequate state support, and insufficient information about the offer.